Teacher Strategy to Increase The Learning Motivation of Public Elementary School Students During The Covid-19 Pandemic: The Stories Of Civil Servant Teachers In 3T District - Meldayani, Andi; Sa'adah, Nurus (CV ODIS, 2021)
The government's efforts to improve education are evenly carried out by appointing teachers with civil servant status in 3T (Lagging, Outermost, and Leading) areas. As an education fighter in the 3T area, there are undoubtedly many obstacles and challenges because the 3T area is not equivalent to other regions in Indonesia, both in terms of people and infrastructure. Therefore, this study aims to find out how the motivation of learning students and how civil servant teachers' strategies improve students' learning motivation. This study uses a descriptive qualitative method. Data collection techniques are non-participation observation techniques, and informants four teachers civil servants in Sekolah Dasar Negeri (SDN) 07 in Durian Air Village Marau District West Kalimantan. The result shows that each teacher has a strategy when giving teaching materials to students so that they do not feel bored and saturated while learning. The presented strategy usually plays while learning, make an agreement so that homework is done alone without the help of parents, give punishment and reward, often praise if the student does the commendable thing, and answer questions. In this way, the students will return to the spirit and be motivated to study in school.